2005
DOI: 10.1093/glycob/cwi071
|View full text |Cite
|
Sign up to set email alerts
|

Polysialic acid facilitates tumor invasion by glioma cells

Abstract: Polysialic acid (PSA) is thought to attenuate neural cell adhesion molecule (NCAM) adhesion, thereby facilitating neural cell migration and regeneration. Although the expression of PSA has been shown to correlate with the progression of certain tumors such as small cell lung carcinoma, there have been no studies to determine the roles of PSA in gliomas, the most common type of primary brain tumor in humans. In this study, we first revealed that among patients with glioma, PSA was detected more frequently in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 40 publications
3
100
0
7
Order By: Relevance
“…The findings could have important implications for human health, as polySia and NCAM are not only expressed on human NK cells but also decorate the surfaces of a variety of tumors and bacteria. For instance, polysialylated NCAM, which is found on a number of cancers including gliomas, small-cell lung carcinomas, and Wilms' tumors, is positively associated with metastasis and disease progression (35)(36)(37). We postulate that tumors co-opt the immune system's strategy of using polySia to modulate responses to chemokines and growth factors, thus gaining a competitive advantage.…”
Section: Discussionmentioning
confidence: 97%
“…The findings could have important implications for human health, as polySia and NCAM are not only expressed on human NK cells but also decorate the surfaces of a variety of tumors and bacteria. For instance, polysialylated NCAM, which is found on a number of cancers including gliomas, small-cell lung carcinomas, and Wilms' tumors, is positively associated with metastasis and disease progression (35)(36)(37). We postulate that tumors co-opt the immune system's strategy of using polySia to modulate responses to chemokines and growth factors, thus gaining a competitive advantage.…”
Section: Discussionmentioning
confidence: 97%
“…Expression of neural cell-adhesion molecule (NCAM) is, for instance, decreased in glioma cells (Andersson et al, 1991;Gratsa et al, 1997;Maidment et al, 1997), and an inverse correlation was found between the expression of one NCAM isoform and the WHOdefined grade of a human glioma cell (Duenisch et al, 2010). NCAM over-expression in tumour astrocytes leads to a significant decrease in their invasive behaviour (Edvardsen et al, 1994;Owens et al, 1998), whereas addition of polysialylated acid (PSA) on NCAM has been shown to facilitate glioma invasion (Suzuki et al, 2005). Finally, PSA-NCAM has been recently proposed as a biomarker for the prognosis of patients with glioblastomas (Amoureux et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies describe a close correlation of polySia-NCAM expression with increased tumour invasion and metastatic potential (Scheidegger et al, 1994;Figarella-Branger et al, 1996;Figarella-Branger et al, 1996;Tanaka et al, 2000;Daniel et al, 2000;Daniel et al, 2001;Trouillas et al, 2003;Suzuki et al, 2005;Amoureux et al, 2010). In all these studies, a role of polySia in promoting tumour cell motility has been inferred from its known role in modulating adhesiveness and migration in the nervous system (Sadoul et al, 1983;Hoffman and Edelman, 1983;Ono et al, 1994;Wang et al, 1994;Hu et al, 1996;Chazal et al, 2000) but the NCAM-dependent or NCAM-independent modulation of tumour cell migration by polySia has been elusive.…”
Section: Discussionmentioning
confidence: 99%